Clinico-epidemiological profile of cardiac admissions at a district level hospital in South Africa: a cohort study - Engelbrecht, Lillian Lize (Department of Medicine, 2025)
Background Nineteen percent of all deaths during 2016 in South Africa (SA), were due to cardiovascular disease. Despite this notable burden, research describing cardiac admissions at the district level is limited and thus, area-specific studies are warranted to provide a perspective on SA's unique population of rich genetic, geographic, social, and cultural diversity. The aim of this study was to describe the epidemiological and clinical characteristics, associated risk factors and outcomes of cardiac patients admitted to a district level hospital in SA, in order to fill the void within currently available literature. Methods We conducted a retrospective records review of all patients admitted to Victoria Hospital Wynberg with a primary cardiac diagnosis, between 1 September 2020 to 30 November 2020. Data were transcribed onto a bespoke data collection form and captured into the Victoria Internal Medicine Research Initiative (VIMRI) electronic registry. The study was approved by UCT HREC (048/2022), the Western Cape Government and Victoria Hospital Board. Results Our cohort consisted of 218 patients (52.8% male) with a mean age (SD) of 60 years (±14.6), and an age range from 22 to 95 years. Acute decompensated heart failure, together with acute coronary syndrome, were responsible for 87.4% of all admissions. The mean length (SD) of stay was 4 days (±3.5 days). Most prevalent risk factors among admitted patients included hypertension (76%), cigarette smoking (55%) and diabetes (42.7%). Amongst diabetics, 27.3% were considered to have acceptable diabetic control (HbA1c £7%). Most frequently reported precipitants for hospital admission were prior inadequate therapy, discontinuing chronic medication, uncontrolled hypertension, disease progression, and ongoing substance use. Twenty-one percent of the cohort were transferred to cardiology for further management and specialist intervention. The inpatient mortality rate was 9.2%, and one-year mortality rate was 18.8%. Readmission within six months was reported amongst 30.8% of our cohort. Discussion and Conclusion Our study provides important insight into the clinico-epidemiological profile of cardiac admissions at a public district level hospital in SA. We report notable rates of morbidity, readmission, and mortality together with a high prevalence of well-known cardiovascular risk factors of hypertension, diabetes mellitus and cigarette smoking. While the in-hospital and one-year mortality rates are notable, but not too unexpected when compared to available data, we nevertheless recommend programmes focused on improving adherence to treatment and optimization of heart failure therapy at a primary care level, as means to reduce rates of poor adherence, suboptimal anti-failure therapy and poor glycaemic control observed in our cohort.